(untitled) (Contemporary Central & East European Law, 2002)
This article is about Polish Constitution and agreement on the topic of polish integration within European Union in future. Polish Lawyers try to make more coherence between Polish and European Union Laws. They try to make some necessary unifications . Most of Poles and especially polish political and juristic elites want to be part of European Union. But doubts within topic of law still remain.